The Digital Era and The Knowledge Revolution: Perspectives From Islamic Epistemology and Islamic Religious Education - Cita Suci; Eva Dewi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This article examines the intersection of the digital era's knowledge revolution and the Islamic epistemological framework, and its implications for Islamic Religious Education (PAI). The digital era described by Manuel Castells as the "network society," Alvin Toffler as the "third wave," and Don Tapscott as the rise of the "Net Generation" has fundamentally transformed how humans acquire, process, and disseminate knowledge. Employing a qualitative library research method with philosophical-analytical content analysis, this article argues that Islamic epistemology which integrates revelation (wahy), reason (aql), the senses (hawas), and intuition (qalb) under the principle of tawhid is capable of critically responding to and correcting the digital knowledge revolution, which tends toward secularism and value-neutrality. The integration-interconnection paradigm (M. Amin Abdullah), Islamization of Knowledge (al-Faruqi), and the concept of ta'dib (al-Attas) serve as the foundational pillars for reconstructing PAI in the digital age. The results show that PAI must transform from mere cognitive transfer toward the cultivation of adab and digital literacy grounded in Islamic values, making technology a tool for da'wah while simultaneously serving as a bulwark against hoaxes, post-truth, and the disruption of scholarly authority. This is an open access article under the CC–BY-SA license